Admission Leukocyte Count is Associated with Late Cardiogenic Shock Development and All-Cause 30-Day Mortality in Patients with St-Elevation Myocardial Infarction. Issue 3 (March 2020) - Klein, Anika; Wiberg, Sebastian; Hassager, Christian; Winther-Jensen, Matilde; Frikke-Schmidt, Ruth; Bang, Lia Evi; Lindholm, Matias Greve; Holmvang, Lene; Moeller-Helgestad, Ole; Ravn, Hanne Berg; Jensen, Lisette Okkels; Kjaergaard, Jesper; et al.
ABSTRACT: Background: Thirty-day mortality in ST-elevation myocardial infarction (STEMI) patients is primarily driven by cardiogenic shock (CS). High neutrophil counts and high neutrophil/lymphocyte ratios (NLR) have previously been associated with mortality in STEMI patients; however, there is only sparse knowledge regarding their association with CS. Purpose: We sought to assess the associations between neutrophil count and NLR with the development of CS as well as 30-day mortality in STEMI patients. Methods: Patients admitted with STEMI at two tertiary Heart Centres throughout 1 year were included in the study and stratified into quartiles according to the level of leukocyte count upon admission. The primary endpoint was development of CS both before (early CS) and after leaving the catheterization laboratory (late CS). The secondary endpoint was all-cause 30-day mortality. Results: A total of 1, 892 STEMI patients were included, whereof 194 (10%) developed CS while 122 (6.4%) died within 30 days. Patients in the highest quartile of neutrophils (OR: 2.54; 95% CI: 1.40–4.60; P  = 0.002) and NLR (OR: 3.64; 95% CI: 2.02–6.54; P <0.0001) were at increased risk of developing late CS compared with patients in the lower quartiles, whereas there was no risk difference across quartiles regarding development of early CS. Both biomarkers correlated strongly to an increased 30-day mortality (plogrank <0.0001) and, moreover, a high level of neutrophils was independently associated with 30-day mortality (HR: 1.95; 95% CI: 1.25–3.03; P  = 0.003). Conclusion: High levels of neutrophils and a high NLR upon admission for STEMI were independently associated with an increased risk of developing late CS and, additionally, both biomarkers showed association to 30-day mortality.